Phosphatidylinositol 3′-Kinase blocks CD95 aggregation and caspase-8 cleavage at the death-inducing signaling complex by modulating lateral diffusion of CD95 - Varadhachary, Arun S.; Krammer, Peter H. (The journal of immunology, 2001)
Activation of phosphatidylinositol 3′-kinase (PI 3′-K) after ligation of CD3 protects Th2 cells from CD95-mediated apoptosis. Here we show that protection is achieved by inhibition of the formation of CD95 aggregates and consequent activation of caspase-8. Inhibition of aggregate formation is mediated by changes in the actin cytoskeleton, which in turn inhibit lateral diffusion of CD95, reducing its diffusion coefficient, D, 10-fold. After cytochalasin D treatment of stimulated cells, the lateral diffusion of CD95 increases to the value measured on unstimulated cells, and CD95 molecules aggregate to process caspase-8 and mediate apoptosis. Regulation of functional receptor formation by modulating lateral diffusion is a novel mechanism for controlling receptor activity.